Two Efficient Block Preconditioners for the Mass-Conserved Ohta-Kawasaki Equation (Advances in Applied Mathematics and Mechanics, 2024)
In this paper, we propose two efficient block preconditioners to solve themass-conserved Ohta-Kawasaki equation with finite element discretization. We alsostudy the spectral distribution of these two preconditioners, i.e., Schur complementpreconditioner and the modified Hermitian and skew-Hermitian splitting (MHSS inshort) preconditioner. Besides, Newton method and Picard method are used to address the implicitly nonlinear term. We rigorously analyze the convergence of Newtonmethod. Finally, we offer numerical examples to support the theoretical analysis andindicate the efficiency of the proposed preconditioners for the mass-conserved Ohta-Kawasaki equation